Perfil de desempenho físico em árbitros da Federação Gaúcha de Futebol de Salão - Rech, Eliana Citolim (2024)
Futsal (indoor football) is characterized as a group sport of high intensity and intermittent actions, which, possibly, was born in Uruguay, around 1940. Corroborating with the physical characteristics required for futsal athletes, futsal referees also need to be fast, dynamic, to possess a great capacity for intermittent endurance, repeated sprint ability and muscular strength. From a scientific point of view, the present study has the potential to support and improve the physical training of referees, resulting in improvements in their performance on the court. Furthermore, by providing a deeper understanding of the physical and cognitive demands faced by referees, it can contribute to the development of more effective and personalized training strategies. Socially, it can raise the quality of the game, strengthening the credibility and attractiveness of futsal as a competitive sport. Based on the facts exposed, the objective of the study is to analyze and relate body composition, agility and aerobic resistance with the physical performance observed in official games of futsal refereesThe sample had 12 referees linked to the Gaucho Futsal Federation, aged between 18 and 55 years, male, who had been training regularly for at least a year and had no history of injury in the last six months. The subjects' body composition was evaluated through body skinfolds, circumferences and diameters; the ability to change direction (agility) through the CODA test; resistance with alternating displacements, through the Assistant Referee Intermittent Endurance Test – ARIET and acceleration and deceleration data during a futsal match, through accelerometry. For statistical analysis, data normality was verified using the Shapiro-Wilk test and data sphericity using the Mauchly test; means and standard deviations of all investigated variables were calculated and simple linear regression tests were performed to verify the relationship between the variables obtained in the physical tests and the anthropometric variables and those obtained by the accelerometer during the official futsal match. The software SPSS 22.0 for Windows (IBM, Chicago, USA) was used, with a significance level of α = 0.05. The results revealed that 42.9% of the ARIET test result can be explained by the subjects' relative body mass, 39.1% of the CODA test result can be explained by the training period of time and 69.4% of the total number of accelerations and decelerations that the referee performs during the game can be explained by the training volume. These findings provide important insights into the factors that influence the performance of futsal referees in specific physical fitness tests and during matches.